Experimental investigation of seismic performance of a novel isostatic frame-cladding system. Issue 5 (April 2022) - Chong, Xun; Huo, Pu; Xie, Linlin; Jiang, Qing; Hou, Linbing; Xie, Jinchen
A new connection measure between the precast concrete (PC) cladding panel and PC frame structure is proposed to realize a new kind of isostatic frame-cladding system. Three full-scale PC wall-frame substructures were tested under the quasi-static load. These substructures included a bare wall-frame specimen, a specimen with a cladding panel that has no opening, and a specimen with a cladding panel that has an opening in it. The damage evolution, failure mode, load-bearing capacity, deformation capacity, and energy dissipation capacity of three specimens were compared. The results indicated that the motions of the cladding panels and the main structures were uncoupled through the relative clearance of the bottom connections, and three specimens exhibited approximately identical failure modes and seismic performance. Thus, the reliability of this new isostatic system was validated.